Petaloid recombinant peptide enhances in vitro cartilage formation by synovial mesenchymal stem cells - Naritomi, Mana (J Orthop Res, 2018)
In vitro chondrogenesis of mesenchymal stem cells (MSCs) mimics in vivo chondrogenesis of MSCs. However, the size of the cartilage pellets that can be attained in vitro is limited by current methods; therefore, some modifications are required to obtain larger pellets. Petaloid pieces of recombinant peptide (petaloid RCP) have the advantage of creating spaces between cells in culture. The RCP used here is based on the alpha‐1 sequence of human collagen type I and contains 12 Arg‐Gly‐Asp motifs. We examined the effect and mechanisms of adding petaloid RCP on the in vitro chondrogenesis of human synovial MSCs by culturing 125k cells with or without 0.125 mg petaloid RCP in chondrogenic medium for 21 days. The cartilage pellets were sequentially analyzed by weight, sulfated glycosaminoglycan content, DNA retention, and histology. Petaloid RCP significantly increased the weight of the cartilage pellets: The petaloid RCP group weighed 7.7 ± 1.2 mg (n = 108), whereas the control group weighed 5.3 ± 1.6 mg. Sulfated glycosaminoglycan and DNA contents were significantly higher in the petaloid RCP group than in the control group. Light and transmission electron microscopy images showed that the petaloid RCP formed the framework of the pellet at day 1, the framework was broken by production of cartilage matrix by the synovial MSCs at day 7, and the cartilage pellet grew larger, with diffuse petaloid RCP remaining, at day 21. Therefore, petaloid RCP formed a framework for the pellet, maintained a higher cell number, and promoted in vitro cartilage formation of synovial MSCs. © 2018 The Authors. Journal of Orthopaedic Research® Published by Wiley Periodicals, Inc. J Orthop Res 37:1350–1357, 2019.